2017
DOI: 10.2174/1381612823666170704123620
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase-1 –targeted Small Molecules, Iron Chelators and Curcumin Analogs as HIV-1 Antivirals

Abstract: Background Despite efficient suppression of HIV-1 replication, current antiviral drugs are not able to eradicate HIV-1 infection. Permanent HIV-1 suppression or complete eradication requires novel biological approaches and therapeutic strategies. Our previous studies showed that HIV-1 transcription is regulated by host cell protein phosphatase-1. We also showed that HIV-1 transcription is sensitive to the reduction of intracellular iron that affects cell cycle-dependent kinase 2. We developed protein phosphata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 118 publications
(153 reference statements)
0
9
0
1
Order By: Relevance
“…Despite this, a clinical study conducted in the 1990s could not find a decreased viral load or increased T-cell count in 40 HIV-patients treated with the molecule for 8 weeks (Gilden and Smart, 1996; James, 1996). Recently, new curcumin derivates or formulations with increased bioavailability and stability were developed against HIV (Kumari et al, 2015; Lin et al, 2017; Sharma et al, 2017; Zhao et al, 2017) and it has been shown that curcumin pretreatment of human genital epithelial cells blocks the infection-mediated induction of chemokines associated with the recruitment of HIV-target cells (Ferreira et al, 2015). Clinical assessment will show, whether these new curcumin variants and mechanisms of protection are effective in humans.…”
Section: Antiviral Activities Of Curcuminmentioning
confidence: 99%
“…Despite this, a clinical study conducted in the 1990s could not find a decreased viral load or increased T-cell count in 40 HIV-patients treated with the molecule for 8 weeks (Gilden and Smart, 1996; James, 1996). Recently, new curcumin derivates or formulations with increased bioavailability and stability were developed against HIV (Kumari et al, 2015; Lin et al, 2017; Sharma et al, 2017; Zhao et al, 2017) and it has been shown that curcumin pretreatment of human genital epithelial cells blocks the infection-mediated induction of chemokines associated with the recruitment of HIV-target cells (Ferreira et al, 2015). Clinical assessment will show, whether these new curcumin variants and mechanisms of protection are effective in humans.…”
Section: Antiviral Activities Of Curcuminmentioning
confidence: 99%
“…The antiviral activity of curcumin has been proven against many enveloped viruses, since this compound is able to modify the lipid bilayer and influences the function of the membrane protein [ 133 ]. The curcumin antiviral effect was confirmed for HBV inhibition of mRNA in HuS-E/2 (50 µM: more than 40%) [ 72 ]; for coxsackie virus (CVB3) in HeLa cells (MOI of 10; 30 µM) [ 134 ] and JEV in Neuro2a cells (MOI of 5; 5 and 10 μM) [ 135 ], acting as a host-target antiviral agent for both of these viruses by modulating ubiquitin–proteasome system; HSV-1 in pretreated VERO cells (MOI of 1; 10 μM) [ 136 ]; HIV by different mechanisms [ 137 ]; HCV entry in Huh-7.5 cells and primary human hepatocytes (IC 50 8.46 ± 1.27 mM in Huh-7.5 and 12.5 µM in PHH) [ 138 ]; and arboviruses like ZIKV and CHIKV in pretreated HeLa cells, inhibiting both infectious particle and viral-RNA (MOI of 0.1; IC 50 : 1.90 and 3.89 μM, respectively) [ 139 ].…”
Section: Curcuminmentioning
confidence: 99%
“…Protein phosphatase-1 (PP1) activity increases HIV-1 transcription, likely because of its effects on iron and HIF-1α. A low level of iron decreases PP1 catalytic activity and increases HIF-1α [218,219]. PP1 also increases HIV-1 transcription by releasing CDK9 from the inactive complex of 7SKRNP and HEXIM1 [220,221].…”
Section: Ferrous Iron (Fe 2+ )mentioning
confidence: 99%